The Role of Government in Efforts to Improve Kuta Beach Tourist Attraction Facilities - I Gusti Ayu Windhautami D; Ida Bgs Gede Agung Widana; I Gede Made Sukariyanto (Indonesian Journal of Interdisciplinary Research in Science and Technology, 2025)
The existence of obstacles related to cleanliness, comfort and infrastructure facilities at Kuta Beach has become a criticism expressed by visitors through various social media platforms, such as Instagram, Tiktok and Youtube. These complaints must of course be addressed and followed up by the local government so that Kuta Beach becomes more organized and managed. This study aims to determine the Role of the Government in Efforts to Improve the Quality of Tourist Attraction Facilities at Kuta Beach, Badung Regency and what challenges and efforts are made by the Government in Efforts to Improve the Quality of Tourist Attraction Facilities at Kuta Beach. The analysis technique used is descriptive qualitative with purposive sampling as a method for determining informants. The informants selected were the Head of the Tourism Destination Division of the Badung Regency Tourism Office, the Head of the Water Resources Division of the PUPR Office of Badung Regency, the Head of the Cleanliness and B3 Waste Management Division of the Environment and Cleanliness Office and the Chairperson of the Regional Tourism Promotion Agency (BPPD) of Badung Regency. The results show that the government plays an active role in improving the quality of Kuta Beach facilities, the government acts as a regulator, implements changes, and motivates stakeholders.